Attitude toward Consumption and Subjective Well‐Being. Issue 1 (14th July 2015) - Iyer, Rajesh; Muncy, James A.
Abstract : The current study looked at the effects of attitude toward consumption (positive or negative) on subjective well‐being. This research studied attitude toward consumption at both the personal (micro) level and societal (macro) level and subjective well‐being in terms of cognitive well‐being and affective well‐being. Results indicated that micro attitudes, whether positive or negative, were positively related to a consumer's subjective well‐being. In contrast, macro attitudes were negatively related to subjective well‐being. We posit that these findings could be due to micro attitudes enhancing the person's feeling of autonomy and control. In contrast, macro attitudes may create concerns beyond the person's control. For those who wish to impact societal‐level consumption, these findings provide empirical support for the idea that focusing on the personal benefits of anticonsumption may be more effective than emphasizing larger societal concerns. We explore the potential implications of these findings for mandated vs. voluntary approaches to reducing consumption.